Need of Fellowship Training in Nepal: Obstetrics and Gynecology Sub-specialties Are Not Left Behind - Dangal, Ganesh; Baral, Gehanath (Nepal Journal of Obstetrics and Gynaecology, 2019)
There is increasing demand of more and more specialized services and trainings in medical field and Obstetrics and Gynecology is not an exception to it. As a sub-specialty training Gynecological oncology and Urogynecology fellowships have become a developmental milestone under National Academy of Medical Sciences since 2018. Resource utilization for academic purpose in public-private-partnership model is beneficial.